Metabolic Diversity in Human Non-Small Cell Lung Cancer Cells - Chen, Pei-Hsuan; Cai, Ling; Huffman, Kenneth; Yang, Chendong; Kim, Jiyeon; Faubert, Brandon; Boroughs, Lindsey; Ko, Bookyung; Sudderth, Jessica; McMillan, Elizabeth A.; Girard, Luc; Chen, Dong; et al. (Molecular cell, 2019)
Intermediary metabolism in cancer cells is regulated by diverse cell-autonomous processes, including signal transduction and gene expression patterns, arising from specific oncogenotypes and cell lineages. Although it is well established that metabolic reprogramming is a hallmark of cancer, we lack a full view of the diversity of metabolic programs in cancer cells and an unbiased assessment of the associations between metabolic pathway preferences and other cell-autonomous processes. Here, we quantified metabolic features, mostly from the 13C enrichment of molecules from central carbon metabolism, in over 80 non-small cell lung cancer (NSCLC) cell lines cultured under identical conditions. Because these cell lines were extensively annotated for oncogenotype, gene expression, protein expression, and therapeutic sensitivity, the resulting database enables the user to uncover new relationships between metabolism and these orthogonal processes. [Display omitted] •Cell-autonomous metabolic diversity is reported in over 80 lung cancer cell lines•Heterogeneous metabolic phenotypes support lung cancer cell growth•Relating metabolic and molecular data uncovers new aspects of metabolic regulation•Some metabolic features predict sensitivity to chemotherapy and targeted agents Metabolic reprogramming influences therapeutic sensitivity in cancer, but the scope of metabolic diversity among cancer cells is unknown. Chen et al. characterized metabolic phenotypes in over 80 non-small cell lung cancer cell lines and then used genomics, transcriptomics, proteomics, and therapeutic sensitivities to uncover relationships between metabolism and orthogonal processes.